DESKRIPSI POTENSI DAN STRATEGI PENGEMBANGAN PARIWISATA DI KOTA BERASTAGI KABUPATEN KARO - Edy Erianto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
Karo regency has alot of tourism potential consist of marine tourism, religious tourism, culture tourism, ecotourism and others. The tourist destination have it’s own appeal for domestic or foreign tourists. The tourist visits increased every year. This study aims to determine the potential and strategy for developing tourism in Karo District. This type of research is qualitative research with a descriptive approach. Research informants were determined purposively. The technique of collecting data was done by observation, interviews and documentation. Analysis data is was with data reduction, presentation of data, conclusion and data triangulation. The data are presented and analyzed in descriptively. The results shows that department of tourism Karo regency have strategy to develop the tourism. Development strategy used such as; Man, for maximize human resources quantity of department of tourism Karo regency, then departmen of tourism has cooperate with stakeholder such as community, agent, blogger, and establish tourism promotion agency for support the tourism marketing.